Tailoring Crystallization Kinetics in Thin Sucrose Films during Convective Drying: Impact of Temperature and Humidity on Onset, Growth, and Nucleation Rate - Martin Schugmann; Petra Foerst (MDPI AG, 2024)
Drying experiments with varying air temperature and humidity were conducted to investigate the influence of the drying process on the crystallization of thin sucrose films. For the first time, the effects of the nucleation onset, nucleation rate, and growth rate were investigated in situ and their differentiated influence on product crystallinity could be assessed. The growth rate was not influenced by air humidity but showed a strong dependence on temperature. It increased with drying temperature; however, at high temperatures, growth was inhibited when the water content falls below a critical level. Noticeable differences in nucleation behavior could be observed with regard to air humidity. Dry air led to crystallization onsets at lower levels of supersaturation, while moderately humid air retarded it. At higher temperatures, nucleation onset commenced at lower water contents but at a constant supersaturation level. The nucleation rate doubled in experiments with moderately humid air (15% RH), while an elevated drying temperature showed generally lower nucleation rates. The observed differences in the nucleation onset and rate could be explained by the film-internal concentration profile, which is strongly influenced by drying parameters. The insights therefore provide a differentiated understanding of the formation of the physical state and how it can be influenced during convective drying.